2021
DOI: 10.1155/2021/8944722
|View full text |Cite
|
Sign up to set email alerts
|

Design, Construction, and Evaluation of the Performance of Dual-Axis Sun Trucker Parabolic Solar Cooker and Comparison of Cooker

Abstract: Energy demand is increasing due to population increment and industrialization. To meet this energy demand, technologies that use renewable energy such as solar energy are being developed. A parabolic solar cooker is one of the main solar cookers, which can cook food and boil water at a high temperature within a short period. This study aimed to design, construct, and evaluate the performance of the constructed parabolic solar cookers. Moreover, this study aimed to compare the constructed cooker with firewood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…The use of thermal oil as the working fluid achieved higher temperatures compared to water. Tibebu and Hailu (2021) designed, constructed, and evaluated the performance of dualaxis sun-tracking parabolic solar cooker and compared the cooker with firewood, charcoal, kerosene, and electricity in terms of cooking time and energy cost of cooking. The study found that the output energy, input energy, efficiency and power of the parabolic solar cooker were 0.182 kW, 1.691 kW, 10.75%, and 0.3 kW/hr, respectively.…”
Section: Previous Studies On Technical Performance Of Solar Cooking S...mentioning
confidence: 99%
“…The use of thermal oil as the working fluid achieved higher temperatures compared to water. Tibebu and Hailu (2021) designed, constructed, and evaluated the performance of dualaxis sun-tracking parabolic solar cooker and compared the cooker with firewood, charcoal, kerosene, and electricity in terms of cooking time and energy cost of cooking. The study found that the output energy, input energy, efficiency and power of the parabolic solar cooker were 0.182 kW, 1.691 kW, 10.75%, and 0.3 kW/hr, respectively.…”
Section: Previous Studies On Technical Performance Of Solar Cooking S...mentioning
confidence: 99%
“…Traditionally, solar cooking solutions use solar thermal energy in solar ovens or cookers, equipment that collects solar radiation and converts it into heat used to cook food. Their mode of operation is based on reflecting solar radiation to a focal area where the pot or pan (or frying pan in some cases) is placed, and/or trapping and absorbing solar radiation in an enclosure that retains the heat [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, widespread concerns have also been raised about the pervasiveness of global warming caused by energy consumption [2]. Unlike fossil fuels, renewable energy sources have several advantages: they replenish themselves naturally, produce little secondary waste, and reduce greenhouse gas emissions and promote sustainability [3,4]. These sources include bioenergy, direct solar energy, geothermal energy, hydropower, wind, and ocean energy (tide and wave) [4].…”
Section: Introductionmentioning
confidence: 99%